2017
DOI: 10.1155/2017/4739793
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of Natural Rubber with Bacterial Cellulose via a Latex Aqueous Microdispersion Process

Abstract: Natural rubber (NR) composites were reinforced with bacterial cellulose (BC) to improve mechanical and physical properties. The natural rubber bacterial cellulose (NRBC) composite films were prepared via a latex aqueous microdispersion process by a thorough mixing of BC slurry with natural rubber latex (NRL). The structural morphology and chemical and physical properties of NRBC composites were investigated. The hydrophilicity, opacity, and crystallinity of the NRBC composites were significantly enhanced becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…Then, composited poly(L-lactic acid) (PLLA) with BC nanofibers covering the sisal fibers were shown to have an elastic modulus and tensile strength higher than the PLLA. Similar procedures to integrate BC-modified sisal fibers have been used for cellulose acetate butyrate matrices [98] and poly acrylated epoxidised soybean oil (polyAESO) [99] to improve the tensile moduli of nanocomposites.…”
Section: Bacterial Cellulose (Bc) Nanofibers-based Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, composited poly(L-lactic acid) (PLLA) with BC nanofibers covering the sisal fibers were shown to have an elastic modulus and tensile strength higher than the PLLA. Similar procedures to integrate BC-modified sisal fibers have been used for cellulose acetate butyrate matrices [98] and poly acrylated epoxidised soybean oil (polyAESO) [99] to improve the tensile moduli of nanocomposites.…”
Section: Bacterial Cellulose (Bc) Nanofibers-based Nanocompositesmentioning
confidence: 99%
“…To improve the mechanical properties of natural rubber, Phomrak et al [99] reinforced the rubber using BC through the process of latex aqueous microdispersion. The hydrophilicity, opacity, and crystallinity of the composite were enhanced by incremental BC loading.…”
Section: Bacterial Cellulose (Bc) Nanofibers-based Nanocompositesmentioning
confidence: 99%
“…In our previous research work, we improved the mechanical and physical properties of natural rubber composite films by reinforcing them with bacterial nanocellulose (BC) via a latex aqueous microdispersion process and found that the tensile strength of NR and BC (NRBC) composite films with BC loaded at 80 wt % was 94% higher than that of pure NR films [ 6 ]. BC is a product from primary metabolism processes of microbes, such as Acetobacter xylinum .…”
Section: Introductionmentioning
confidence: 99%
“…BC is a product from primary metabolism processes of microbes, such as Acetobacter xylinum . BC has been extensively reported as having unique properties, including high mechanical strength, high water absorption capacity and high crystallinity [ 6 , 7 , 8 ]. BC is also widely used as biomaterials for medicinal purposes [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that HO modified MWCNT has shown high dispersion than MWCNT. Phomrak and Phisalaphong [18] attempted with bacterial cellulose (BC) to reinforce the NR latex and concluded that the tensile strength was increased 94% higher than pure NR latex. Medina et al [19] prepared a glass fiber reinforced composite using CNTs doped epoxy and concluded that incorporation of CNTs increased the hardness by 6% and decreased the fracture toughness by 17%.…”
Section: Introductionmentioning
confidence: 99%